Estudio de microbiomas en ámbitos médicos-asistenciales por microscopía electrónica de barrido - D'arpino, María Cecilia (2021)
The identification of microbiomes present in the health field is extremely important given the close relationship with human diseases. The aim of this study was to investigate the composition of microorganisms on the laboratory surfaces of the Central Blood Bank "Dr. César Guerra", (PRIS-SI.PRO.SA). Duplicate samples from the countertops, air conditioners and the equipment on the Production, Distribution and Molecular Biology services were taken using paper tape and swabs. Plating was carried out in LB pH7 culture medium containing Cycloheximide (CH) and Cyclohehimide/ Nalidixic Acid (CH / NA) antibiotics. Both the paper tape and the colonies obtained from the cultures were subjected to Scanning Electron Microscopy (SEM). Sampling using paper tape allowed the presence of microbial biofilms to be detected in the internal part of the Production service centrifuge, in the Distribution service platelet shaker and in the Molecular Biology service countertops. They presented a complex three-dimensional organization characterized by microorganisms of different morphology arranged in layers immersed in abundant extracellular material. The tape analysis also revealed the presence of isolated bacteria (cocci and bacilli) or the formation of small groups of them at the different sampling sites. The cultures allowed isolating predominant microorganisms from countertops, air conditioners and equipment. A total of 45 colonies (gram + and gram -) that exhibited various morphotypes (cocci, bacilli and cocobacilli) were isolated. Using SEM, it was possible to analyze in detail the structure, organization and morphology of the bacteria in culture. Furthermore, it was observed that many colonies established close contacts. The SEM study revealed a wide spectrum of relationships among them. It was possible to analyze the contact points among interacting colonies, revealing morphological changes in the bacteria as well as a large amount of extracellular material at the interaction sites. In addition, the topographic analysis of the colonies showed differences in the conformation of the different sectors in some of them. This work, aimed at analyzing the microbiological communities developed in situ in healthcare settings, proposes high-resolution microscopy techniques as key tools for the study in situ of biofilms on a surface, which study is lacking in our country.